Increasing the business potential of companies by ensuring continuity of the development of their information systems by current information technologies - Tvrdíková, Milena (Journal of Business Economics and Management, 2016)
This paper deals with applications of information and communication technologies in the management of companies and institutions. It also focuses on Competitive Intelligence and Business Intelligence and the description of their position in business management. The paper presents current trends in information and communication technologies with emphasis on the use of virtualization and Cloud Computing technologies. The author discusses the importance of Cloud Computing to maintain the continuity of information system of enterprises with low financial impact, thereby increasing its stability. Theoretical framework and literature support the assumption that information and communication technologies are essential for the competitiveness of small and mediumsized enterprises. Discussed are factors that affect management and use of information and communication technologies in small and medium-sized enterprises, in particular the use of cloud computing. Based on the results obtained from a questionnaire survey carried out in the Czech Republic, the author proposed methodological recommendations to facilitate the transition to cloud computing.